2021
DOI: 10.3390/atmos12101366
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of the COVID-19 Lockdown Measures on the 2020 Columnar and Surface Air Pollution Parameters over South-Eastern Italy

Abstract: The combined use of Lecce-University AERONET-photometer measurements and PM2.5, PM10, NO2, CO, and SO2 concentrations from different sites of Apulia-Region Air-Quality Agency represents the peculiarity of this study, which evaluates the impact of COVID-19 lockdown (LD) measures on aerosol and gaseous pollutants. Monthly-averaged columnar and surface parameters of the 2020-year were compared with corresponding monthly parameters of the ref-year obtained by averaging 2017, 2018, and 2019 measurements in order to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 64 publications
2
1
0
Order By: Relevance
“…These results indicate that the column aerosol was not significantly affected immediately after the introduction of the restrictions but rather in a later period after the removal of the most restrictive measures in most European countries. Similar behaviour was observed at several sites in south-eastern Italy [45] and in Paris [46]. This fact could be due to the fact that most atmospheric particles are not directly emitted into the atmosphere, as is the case for gaseous pollutants [68,69].…”
Section: Aesupporting
confidence: 77%
See 1 more Smart Citation
“…These results indicate that the column aerosol was not significantly affected immediately after the introduction of the restrictions but rather in a later period after the removal of the most restrictive measures in most European countries. Similar behaviour was observed at several sites in south-eastern Italy [45] and in Paris [46]. This fact could be due to the fact that most atmospheric particles are not directly emitted into the atmosphere, as is the case for gaseous pollutants [68,69].…”
Section: Aesupporting
confidence: 77%
“…Regarding the studies of column aerosol, the AERONET measurements showed that, while AOD decreased in Italy [45] during the lockdown, it increased in France [46]. These measurements were in line with MODIS satellite measurements, which observed a significant reduction in AOD in Poland [47] and most areas in Europe, except for its western part, where it increased [10,11].…”
Section: Introductionsupporting
confidence: 78%
“…The PM investigation in the city of Lecce has been carried out in several studies [9][10][11][12], where primary and secondary contributions to PM by means of bulk chemical analyses were carried out. Bulk chemical analyses provide averaged information on the composition of the PM, and it is possible to trace the emission sources through statistical approaches by considering the correlations between the analytes present in the sample.…”
Section: Introductionmentioning
confidence: 99%